2010
DOI: 10.1364/oe.18.00a536
|View full text |Cite
|
Sign up to set email alerts
|

Patterned dye structures limit reabsorption in luminescent solar concentrators

Abstract: Abstract:This work describes a method for limiting internal losses of a luminescent solar concentrator (LSC) due to reabsorption through patterning the fluorescent dye doped coating of the LSC. By engineering the dye coating into regular line patterns with fill factors ranging from 20 -80%, the surface coverage of the dye molecules were reduced, thereby decreasing the probability of the re-emitted light encountering another dye molecule and the probability of reabsorption. Two types of fluorescent dyes with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…A freestanding film that did not contain SPA did not show any change in volume after exposure to light. Furthermore, a film that contained a non-photochromic commercial dye instead of SPA showed a similar absorption spectrum (K160, l max = 450 nm) [23] and did not shrink upon light illumination. This behaviour indicates that the shrinkage of the SPA hydrogels is not a result of absorbed light, which is transferred into heat, but rather is related to the photoresponsive change in the hydrophobicity of the spiropyran dye.…”
Section: Resultsmentioning
confidence: 98%
“…A freestanding film that did not contain SPA did not show any change in volume after exposure to light. Furthermore, a film that contained a non-photochromic commercial dye instead of SPA showed a similar absorption spectrum (K160, l max = 450 nm) [23] and did not shrink upon light illumination. This behaviour indicates that the shrinkage of the SPA hydrogels is not a result of absorbed light, which is transferred into heat, but rather is related to the photoresponsive change in the hydrophobicity of the spiropyran dye.…”
Section: Resultsmentioning
confidence: 98%
“…Tsoi et al [22,23] demonstrated that patterning the luminophore on a clear waveguide can reduce the amount of re-absorption events. To investigate the influence of re-absorptions on our previous measurements, we determined the impact of adding cholesteric reflectors to patterned LSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by the approach reported for an LSC, 35 we propose to pattern the phosphor layer and place a remote After the forward flux is reflected by the remote reflector, the probability of the reflected flux crossing the phosphor layer can be made close to zero. Hence, the factor T ex α(λ,θ) approaches unity.…”
Section: B Numerical Examplementioning
confidence: 99%
“…The idea of patterning a phosphor layer has been studied for reducing self-absorption. 35 Waveguiding is also important in a different context: an LSC utilizes the PL photons trapped inside. Probability of trapping light has been modeled for both isotropic emission and electric dipole emission.…”
Section: Introductionmentioning
confidence: 99%